Negative perceptions toward older adults and life satisfaction among community-dwelling older citizens in Japan [version 2; peer review: 1 approved, 2 approved with reservations] - Yuho Shimizu; Hiroyuki Suzuki; Tomoki Furuya; Ai Iizuka; Keigo Hinakura; Tomoya Takahashi; Yan Li; Daichi Yamashiro; Yoshifumi Takahashi; Daisuke Cho; Susumu Ogawa; Kenichiro Sato (F1000Research)
Background With the rapid aging of the population, increasing life satisfaction among older adults is essential. Negative perceptions of older adults are internalized, leading to poor mental health. This study hypothesized that participants with more negative perceptions of older adults would have lower life satisfaction. Methods A cross-sectional survey of older adults was conducted across five wards and four cities in Tokyo, Japan. Participants responded to questions regarding demographics, life satisfaction, and negative perceptions of older adults. Data from 285 participants (264 women, M = 71.97 years) were analyzed. Results The intraclass correlation coefficient for life satisfaction concerning residential areas was. 03 (95% confidence interval [CI] = [-.03, .10]). Instead of multilevel models, a multiple regression model with life satisfaction as the dependent variable and negative perceptions of older adults and demographics as the independent variables yielded the best fit. Results indicated that participants with more negative perceptions of older adults reported lower life satisfaction (β = -.16, 95% CI = [-.28, -.04], p = .008), supporting our hypothesis. Conclusions This study was constrained by limited variance in residential areas and a predominantly female participant pool. Previous studies have shown that higher life satisfaction is associated with increased social participation and extended life expectancy, and interventions aimed at enhancing life satisfaction in older adults are significant. Further exploration is warranted to ascertain whether a causal relationship exists, wherein more negative perceptions of older adults diminish life satisfaction.